Educação sufocada: os impactos da Covid-19 nas atividades educacionais de unidades prisionais brasileiras - Luz Bisneta, Beatriz Xavier Macedo da (2021)
In the middle of March 2020, the world began to live with the effects of the new coronavirus pandemic. The efforts expended by the responsible authorities were concentrated on non-pharmacological measures for the prevention of the transmission of the disease, such as social distancing. The collapse caused by the COVID-19 resulted in the cancelling of classes in schools and universities, affecting more than 90% of students worldwide (UNESCO, 2020). The impacts of these measures were felt massively by the most vulnerable populations, such as those people deprived of their liberty. The present study, based on documental research, including written sources (official documents or those produced on the basis of daily experience) and visual sources (maps, photographs, amongst others), was initiated in May 2020 and concluded in May 2021. In the light of theoretical contributions from Achille Mbembe, Karl Marx, Michel Foucault and Paulo Freire, it proposes a theoretical-reflexive approach, as a way of demonstrating that the offer of educational activities in the prison system – guaranteed by public policy- suffered an expressive process of degradation during the period of the pandemic, which represented yet another, amongst the many omissions of the State in relation to this group, and produced malevolent effects with respect to the dignity of the human being and to the right of the prisoner to social reintegration.